The effect of using dual screen computer panel to the neck-shoulder muscle activity among group of students - Mohd Tamrin, Shamsul Bahri; Akir, Nur Fitriyah; Ng, Yee Guan; How, Vivien; Zolkifli, Nur Zuhairiza (Tehran University of Medical Sciences, 2016)
Background: Workstation design has shift from using single monitor screen to dual monitor screens, which may impose some impacts towards the muscles activity. This study aimed to determine the effect of using dual monitor screen computer to the neck-shoulder muscle activity among computer user.